A Seizure Care Pathway in the Emergency Department: Preliminary Quality and Safety Improvements. (29th May 2012) - Iyer, Parameswaran M.; McNamara, Patricia H.; Fitzgerald, Margaret; Smyth, Liam; Dardis, Christopher; Jawad, Tania; Plunkett, Patrick K.; Doherty, Colin P.
Abstract : Aim . To evaluate the utility of a seizure care pathway for seizure presentations to the emergency department (ED) in order to safely avoid unnecessary admission and to provide early diagnostic and therapeutic guidance and minimize length of stay in those admitted. Methods . 3 studies were conducted, 2 baseline audits and a 12-month intervention study and prospective data was collected over a 12-month period (Nov 2008-09). Results . Use of the Pathway resulted in a reduction in the number of epilepsy related admissions from 341 in 2004 to 276 in 2009 (P = 0.0006 ); a reduction in the median length of stay of those admittedfrom 4-5 days in the baseline audits to 2 days in the intervention study (P ≤ 0.001 ); an improvement in time to diagnostic investigations such as CT brain, MRI brain and Electroencephalography (P ≤ 0.001, P ≤ 0.048, P ≤ 0.001 ); a reduction in readmission rates from 45.1% to 8.9% (P ≤ 0.001 ); and an improvement in follow-up times from a median of 16 weeks to 5 weeks (P < 0.001 ). From a safety perspective there were no deaths in the early discharged group after 12 months follow-up. Conclusion . The burden of seizure related admissions through the ED can be improved in a safe and effective manner by the provision of a seizure care pathway.